A RFID-enabled positioning system in automated guided vehicle for smart factories. (July 2017) - Lu, Shaoping; Xu, Chen; Zhong, Ray Y.; Wang, Lihui
Highlights: Two parking antennas group can adjust vehicle directions in an AGV. Different diameter antennas are tested in sparse and intensive tags area. Sparse tags layout is tested suitable for large antennas in the driving zone. Intensive tags layout is suitable for small antennas in the parking zone. Abstract: Smart factory, as one of key future for our industry, requires logistics automation within a manufacturing site such as a shop floor. Automated guided vehicle (AGV) systems may be one solution, whose accuracy will be influenced by some factors. This paper presents a radio frequency identification (RFID)-enabled positioning system in AGV for smart factory. Key impact factors on AGV's accuracy such as magnetic field in circular antenna, circular magnetic field, and circular contours stability are examined quantitatively. Based on the examinations, simulation studies and a testbed are carried out to evaluate the feasibility and practicality of the proposed approach. It is observed that large diameter antennas are used in driving zone and small diameter antennas are used in parking zone. This approach was compared with another method using passive RFID tags and it is superior to that method with greatly reduced tags' deployment. Observations and lessons from simulation and testbed studies could be used for guiding automatic logistics within a smart manufacturing shop floor.